ANTI-DIABETIC EFFECT OF A NOVEL NANO POLYMER OF THYMOL IN STREPTOZOTOCIN-INDUCED DIABETIC WISTAR RATS - KARIMI, ELAHE; ABBASI, SHAHRYAR; AIDY, ALI; GHANEIALVAR, HORI; MOHAMMADPOUR, SHAHRAM; AKHAVAN, MAZIAR MOHAMMAD; ABBASI, NASER (International Journal of Applied Pharmaceutics, 2019)
Objective: The aim of this study was to evaluate the effect of thymol and thymol nano polymer on the blood biochemical parameters and anti-diabetic activity in Streptozotocin (STZ)-induced diabetic rats. Methods: The synthesized nano polymer (NP) was characterized by using different spectroscopy methods, such as IR, HNMR and CNMR. Loading and releasing of thymol were investigated by HPLC. Eleven groups of the Streptozotocin-induced diabetic and normal rats (overall 110 males) were tested through various biochemical factors such as: serum glucose, insulin, liver function-related enzymes including ALT, AST, ALP and bilirubin by ELISA kit methods. Results: It has shown that thymol nano polymer is desirable for transferring drug. The amount of thymol loaded on NP estimated at 43±2.5 %. Then, 65% of the loaded drug was released. LD50 for thymol and thymol nano polymer were 435 and 583 mg/kg, respectively. thymol nano polymer at doses of 30, 60 and 90 mg/kg, in a dose-dependent manner, reduced blood glucose, increased insulin levels, and controlled liver enzymes ALT, AST, ALP and bilirubin in the STZ-induced diabetic rats. Conclusion: The use of thymol nano polymer appears to be a new aspect concerning to protect diabetes-induced damage in the animal model.